Phenethyl Isothiocyanate-Containing Carbomer Gel for Use against Squamous Cell Carcinoma - Ositomiwa O. Osipitan; Yi Shi; Anthony J. Di Pasqua (MDPI AG, 2021)
It is currently estimated that one in every five Americans will develop skin cancer during their lifetime. Squamous cell carcinoma (SCC) is a common type of skin cancer that can develop due to the skin's exposure to the sun. Herein, we prepared a topical gel containing 0.5% v/w phenethyl isothiocyanate (PEITC) for the treatment of SCC. PEITC is a naturally occurring isothiocyanate that has been shown to have efficacy against various types of cancer in preclinical studies. We first incorporated PEITC into a carbomer gel. A uniform formulation was prepared, and its viscosity was appropriate for topical application. We then demonstrated the release of PEITC from the gel into and through a Strat-M skin-like membrane. Finally, the effects of the PEITC-containing gel were tested against SCC and normal keratinocytes skin cells in culture, and these results were compared to those obtained for free 5-fluoruracil (5-FU), a commonly used skin-cancer drug. Our results show that a homogeneous PEITC-containing topical gel can be prepared and used to kill SCC cells. Thus, our formulation may be useful for treating SCC in the clinic.